Co‐incidental C9orf72 expansion mutation‐related frontotemporal lobar degeneration pathology and sporadic Creutzfeldt−Jakob disease. (1st December 2020) - Klotz, Sigrid; König, Theresa; Erdler, Marcus; Ulram, Andreas; Nguyen, Anita; Ströbel, Thomas; Zimprich, Alexander; Stögmann, Elisabeth; Regelsberger, Günther; Höftberger, Romana; Budka, Herbert; Kovacs, Gabor G.; et al.
Abstract: Background: The C9orf72 hexanucleotide expansion mutation is the most common cause of genetic frontotemporal dementia (FTD), amyotrophic lateral sclerosis (ALS) and combined FTD‐ALS. Its underlying neuropathology combines TDP‐43 pathology and dipeptide repeat protein (DPR) deposits and may also associate with other neurodegeneration‐associated protein aggregates. Herein we present a unique combination of C9orf72 mutation with sporadic Creutzfeldt−Jakob disease (CJD) in a 74‐year‐old patient with rapidly progressive dementia. Methods: Detailed neuropathological examination including immunohistochemistry for several proteinopathies. Genetic analysis was conducted by repeat primed polymerase chain reaction (PCR). Furthermore, we analyzed additional C9orf72 mutation carriers for prion−protein (PrP) deposits in brain tissue and screened the cerebellar cortex of other CJD cases for p62/DPR neuronal inclusions to assess the frequency of combined pathologies. Results: Postmortem brain examination of a patient with a rapidly progressive neurological deterioration of 8 months' duration confirmed the diagnosis of CJD. She harbored valine homozygosity at PRNP codon 129. In addition, a frontotemporal lobar degeneration (FTLD)‐pattern with TDP‐43 protein aggregates and p62+/C9RANT+ positive inclusions along with a high degree of Alzheimer‐related pathology (A3B3C3) were identified. The suspected C9orf72 expansion mutation was confirmed by repeat‐primed PCR. Screening of 13 C9orf72 cases showed no pathological PrP aggregates and screening of 100 CJD cases revealed no other C9orf72 expansion mutation carriers. Conclusion: A combination of a C9orf72 expansion mutation‐related FTLD with sporadic CJD in the same patient is rare. While the rarity of both diseases makes this concurrence most likely to be coincidental, questions regarding a potential link between these two neurodegenerative pathologies deserve further studies. Abstract : We describe clinicopathological features of a patient with co‐incident C9orf72 expansion mutation‐related FTLD‐pathology and sporadic Creutzfeldt−Jakob disease (sCJD). This combination has not been described to date.